Cross-Platform Reactions to the Post-January 6 Deplatforming - Cody Buntain; Martin Innes; Tamar Mitts; Jacob Shapiro (Journal of Quantitative Description: Digital Media)
We study changes in social media usage following the ‘Great Deplatforming’ in the aftermath of the 6 January 2021 attack on the US Capitol. Following the attack, several major platforms banned thousands of accounts, ostensibly to limit misinformation about voter fraud and suppress calls for violence. At the same time, alternative platforms like Gab, BitChute, and Parler welcomed these deplatformed individuals. We identify three key patterns: First, in studying the platforms that emerged among users seeking alternative spaces, we see high frequencies of users bridging these communities announcing their intent to join non-mainstream platforms to their audiences on mainstream platforms. Second, focusing on platforms that were created to be alternative, anti-censorship spaces, deplatforming preceded a sustained increase in engagement with Gab across Twitter, Reddit, and Google search, while Parler saw a steep decline in engagement. Third, examining the language in these spaces, toxic discourse increased briefly on Reddit and Twitter but returned to normal after the deplatforming, while Gab became more toxic. These results suggest that while deplatforming may precede a reduction in targeted discussions within a specific platform, it can incentivize users to seek alternative platforms where these discussions are less regulated and often more extreme. As these alternative spaces are often more political and extreme than their mainstream counterparts, deplatforming may drive single-platform improvements at the expense of the larger information ecosystem.